Development of Web-Based Building Permit (IMB) Information System - Muhammad Syarifuddin Noor; Irfan Prasetia (Jurnal Teknologi Berkelanjutan, 2021)
An integrated information management system is needed to provide convenience not only for organizers but also can provide information such as completion time, costs, and procedures that can be informed directly and transparently. The purpose of this research is to find out the obstacles faced and to design a web-based building permit (IMB) information system with mobile features to speed up the IMB creation process. The research method used is the waterfall model method. The method used to analyze the problems and constraints in the process of making the IMB by the Frontliner, Head of Section, the Technical Team, and the Head of the IMB by experimenting with the application of the IMB Issuance Information System. From the data that has been obtained, an information system design is carried out with the stages of requirements, design, analysis, design, coding, system implementation, system verification, and validation. The results of this study obtained a web-based IMB information system design to facilitate the process of issuing IMB. With the existence of a management information system, IMB proposals based on the results of verification and validation can be applied and provide convenience and speed up the IMB management process.